Razširjenost dnevnih metuljev (Lepidoptera: Rhopalocera) na Goričkem (severozahodna Slovenija) - Verovnik, Rudi (Natura Sloveniae, 2000)
Results of the fieldwork of the group for lepidopterology at Student Research Camp Šalovci 99' and previous observations in year 1999 are presented. Altogether 75 species of butterflies were recorded on 29.5.1999 and between 22.7.1999 and 29.7.1999 from 60 localities including individual observations. Taking into account the published data 7 new species for Goričko were observedraising the number to total of 109 registered species. Apart from thatfindings of 2 species, previously listed without exact locality, were confirmed. Altogether 9 species included in the Atlas of endangered butterfly species of Slovenia were sighted. The vitality of population of Maculinea alcon Schiff have been estimated by egg counts. Some of the Slovenian endangered butterflies from families Lycaenidae and Nymphalidae are still common at Goričko, probably due to extensive land use. Most surprising were the findings of thermophylous species that occur mostly locally at Goričko. Because of species richness and last areas of continuos distribution of some highly endangered species in Slovenia, complete protection of Goričko is required.
Keywords: Butterflies; Ecosystem; Goričko; metulji; zoogeografija; zoologija; zoology